Database management systems - Ward, Patricia (Thomson, 2006)
This is a modern, concise and accessible introduction to database systems for computing students. Designed to cover a one semester course, core topic coverage is motivated by plenty of examples (using Oracle 10g) and practical guidelines. The material is up-to-date and grounded in today’s modern enterprise infrastructure where databases need to link to a Web front end. Providing concise yet full coverage for a one semester course, the examples and activities are efficient exam preparation tools for computing students on a database course. Developed with support from Middlesex University Press and Global Campus